Campylobacter jejuni Biofilm Formation Under Aerobic Conditions and Inhibition by ZnO Nanoparticles - Zhong, Xian; Wu, Qingping; Zhang, Jumei; Ma, Zonghao; Wang, Juan; Nie, Xiang; Ding, Yu; Xue, Liang; Chen, Moutong; Wu, Shi; Wei, Xianhu; Zhang, Youxiong (Frontiers in Microbiology, 2020)
Campylobacter jejuni is a major foodborne pathogen worldwide. As it forms biofilms, it can become a persistent contaminant in the food and pharmaceutical industries. In this study, it was demonstrated that C. jejuni could make more biofilm in aerobic conditions than in microaerobic conditions, and only 13.9% C. jejuni entered coccus (a VBNC state) under microaerobic conditions; however, the rate increased to 95.5% under aerobic conditions. C. jejuni could form more biofilm in mixed culture with Escherichia coli or Pseudomonas aeruginosa than in pure culture. Scanning electron microscope results showed that C. jejuni retained its normal spiral shape under aerobic conditions for 48 h by forming crosslinks with the aerobic and facultative anaerobic bacteria. Additionally, culture medium containing 0.5 mg/ml ZnO nanoparticles inhibited biofilm formation. Our results provide information on a new approach to controlling contamination via C. jejuni.